Psychogenic Nonepileptic Spells in Chronic Epilepsy Patients with Moderate Cognitive Impairment: The Need for Video EEG Monitoring for Adequate Diagnosis - Robinson, Diana Mungall; Kirmani, Batool F. (Case Reports in Psychiatry, 2014)
The objective of our study was to emphasize the importance of intensive video EEG monitoring in patients with a well-established diagnosis of epilepsy with moderate cognitive impairment. The idea was to diagnose new onset frequent atypical events prompting the need for frequent emergency room and clinic visits and hospital admissions. Retrospective chart reviews were conducted on patients with chronic epilepsy with moderate cognitive impairment who had an increased incidence of new onset episodes different from the baseline seizures. Data were acquired from electronic medical records. The hospital’s Institutional Review Board gave approval for this retrospective analysis of patient records. We retrospectively analyzed data from three patients with an established diagnosis of epilepsy. Extensive chart reviews were performed with emphasis on type and duration of epilepsy and description of baseline seizures and description of new events. There were two men and one woman with moderate cognitive impairment. One subject had generalized epilepsy and other two had temporal lobe epilepsy. The patients were on an average of two to three antiepileptic medicines. The duration of follow-up in our neurology clinic ranged from 9 months to 5 years. The occurrence of increased frequency of these atypical events as described by the caregivers, despite therapeutic anticonvulsant levels, prompted the need for 5-day intensive video EEG monitoring. New atypical spells were documented in all three patients and the brain waves were normal during those episodes. The diagnosis of pseudoseizures was made based on the data acquired during the epilepsy monitoring unit stay. Our data analysis showed that intensive video EEG monitoring is an important tool to evaluate change in frequency and description of seizures even in cognitively impaired patients with an established diagnosis of epilepsy for adequate seizure management.